ABDIMAS USAHA LADRANG DESA BAJERA, SELEMADEG, TABANAN - Mendra, Ni Putu Yuria; Praganingrum, Tjokorda Istri (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
Chips is one type of snack loved by people both lower, middle, and upper. Chips are many kinds of one of them there is called onion chips, which is more famous by the name "Ladrang". Ladrang has a delicious flavor and tasty, so that from small children to parents are very fond of this type of snack. Along with the many parties who menggemarinya, then ladrang can be a business opportunity. Tabanan area especially Bajera most mother-mother have business that is as maker and seller ladrang. One of the moves in this ladrang business is Desak Made Artasih which is more famously called Bu Dewa. Since 1998. Bu Dewa started the business of making the ladrang.Partner issues are in production and management aspects including 1) partners do not have spice blender, where the partners are still using cobek and ulekan to smooth the mixing seasoning, 2) the partner has not used the onion slicer to slicing the onion, so far the partners only use the knife 3) the partner has only one stove with a small axis for frying, 4) the frying pan is old and damaged, 5) the partner does not have the means to remove the remaining oil in ladrang 6) has not used the apron and the slippers for cleanliness and security , 7) partners do not have promotional means such as business cards and nameplate, 8) partners still use streples to wrap, and 9) do not have bookkeeping.The solution provided includes 1) the procurement of one spice blender, 2) the procurement of one onion slicer, 3) the addition of one large axle stove, 4) the provision of one large frying pan for frying ladrang, 5) procuring oil slicer, 6) procuring two apron and two slippers, 7) procurement of promotional means for partners in the form of packaging, business name and business cards, 8) procurement of one press machine (hand sealer), 9) procurement of two cash books and simple bookkeeping training.